2010
DOI: 10.1002/ijc.24853
|View full text |Cite|
|
Sign up to set email alerts
|

Ursodeoxycholic acid switches oxaliplatin‐induced necrosis to apoptosis by inhibiting reactive oxygen species production and activating p53‐caspase 8 pathway in HepG2 hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is resistant to chemotherapy. Recently, however, several oxaliplatin-based combinatorial treatments have shown a promising anti-tumor activity in patients with HCC. Presently, we demonstrate that oxaliplatin triggers necrosis more than apoptosis in HepG2, SK-Hep1, SNU-423 and Hep3B HCC cells, while mainly inducing apoptosis in HCT116 and HT29 colon cancer cells. Interestingly, ursodeoxycholic acid (UDCA), a less hydrophobic bile acid that can suppress carcinogenesis, shifted oxal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 66 publications
3
48
0
2
Order By: Relevance
“…Compared to the control, hypoxia did not reduce ATP availability in those incubated with low-dose CSE, implicating ATP presence as mode of apoptosis-necrosis switch similar as previously described [34,35]. Moreover, Lim et al reported a switch from necrosis to apoptosis based on inhibition of ROS production in hepatocellular carcinoma [36]. We observed significant lower presence of ROS in hypoxia unaffected by CSE incubation.…”
Section: Discussionsupporting
confidence: 69%
“…Compared to the control, hypoxia did not reduce ATP availability in those incubated with low-dose CSE, implicating ATP presence as mode of apoptosis-necrosis switch similar as previously described [34,35]. Moreover, Lim et al reported a switch from necrosis to apoptosis based on inhibition of ROS production in hepatocellular carcinoma [36]. We observed significant lower presence of ROS in hypoxia unaffected by CSE incubation.…”
Section: Discussionsupporting
confidence: 69%
“…A major clinical issue affecting 10-40 % of patients treated with oxaliplatin is severe peripheral neuropathy causing sensory, motor, and autonomic dysfunction, with symptoms including cold sensitivity and neuropathic pain (Al Moundhri et al 2013). The treatment of brain mitochondria with Oxa provokes several responses including membrane peroxidation and dysfunction of the mitochondria Lim et al 2010). In the current study, we investigated the plausible role of mitochondrial oxidative stress and respiratory chain mechanisms in Oxa-induced brain mitochondrial toxicity.…”
Section: Discussionmentioning
confidence: 98%
“…76). It has been demonstrated that oxaliplatin can activate both apoptosis and necrosis depending on the cellular model (77). Although there is a lack of literature about it, in a recent work from Grassilli and colleagues, it was demonstrated that glycogen synthase 3 b (GSK3B), a serine-threonine kinase belonging to the glycogen synthase kinase subfamily that is involved in energy metabolism, neuronal cell development, and body pattern formation, was activated in almost 50% of colon carcinomas and in two thirds of drug-resistant ones.…”
Section: Regulated Necrosismentioning
confidence: 99%